The how and the when of semantic illusions in native and non-native languages - Ana I. Fernandes; Juliana Novo Gomes; Juan Haro; Cristina Flores; Montserrat Comesaña (Language and Cognition)
The nature and processing of semantic illusions (SI; when speakers fail to notice an anomalous word in a sentence that is contextually perfectly aligned with world knowledge) have been largely studied during first language comprehension. Although this issue is not free of controversy, findings sustain The Node Structure Theory, according to which SI is a phonological and/or semantic priming effect which occurs due to phonological and/or semantic links existing between the correct and the anomalous word. However, the question as to whether the same underlying mechanisms can be found in bilinguals and whether the effect is modulated by age of language acquisition (AoA) and language dominance remains unexplored. The aim of this study was to examine this issue on sequential European Portuguese-German bilinguals (and their respective control groups) using a self-paced reading paradigm. The sentences’ language, AoA (early vs. late), and type of target word used (correct vs. anomalous) were manipulated. Results showed the occurrence of SI, independently of language and AoA. Therefore, findings suggest that SI occur due to a semantic overlap between critical words and are similarly processed in L1 and L2.